2012
DOI: 10.2225/vol15-issue5-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the expression of defence genes in Carica papaya fruit by methyl jasmonate and low temperature treatments

Abstract: The defence mechanisms that are activated by methyl jasmonate (MJ) in fruits are not well understood. In this work, we studied the expression of defence genes in papaya fruit that are induced by the exposure to MJ and/or low temperatures. The papaya fruits 'Maradol' were randomly divided into two groups: one group was the untreated control and the other was treated with 10 -4 M of MJ. Half of the fruits from each of the two groups were stored after treatment for 5 days at 5ºC and 2 days at 20ºC. We studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…7 However, these findings need to be further validated with other strategies, such as MeJA, which showed remarkable amelioration of IB in diverse fruit species, such as banana peel, peach, loquat, and mango fruit. 35,40,41,48,50 As for the mechanism of MeJA-induced chilling tolerance, many studies focused on its effects on fruit under cold conditions; however, less attention was paid on CI of fruit after cold removal. In this study, IB alleviation induced by MeJA was observed in peach fruit at the end of shelf life after cold storage for 63 days (Figure 1A); we further confirm that both phenolic metabolism and lipid reprogramming events are involved in CI alleviation processes and provide more details to understand CI.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, these findings need to be further validated with other strategies, such as MeJA, which showed remarkable amelioration of IB in diverse fruit species, such as banana peel, peach, loquat, and mango fruit. 35,40,41,48,50 As for the mechanism of MeJA-induced chilling tolerance, many studies focused on its effects on fruit under cold conditions; however, less attention was paid on CI of fruit after cold removal. In this study, IB alleviation induced by MeJA was observed in peach fruit at the end of shelf life after cold storage for 63 days (Figure 1A); we further confirm that both phenolic metabolism and lipid reprogramming events are involved in CI alleviation processes and provide more details to understand CI.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Among diverse strategies against CI, phytohormone treatments often confer effects of CI alleviation and quality on an extensive range of horticultural products, including ethylene, abscisic acid, gibberellin acid, , melatonin, , brassinosteroids, , salicylic acid, and jasmonic acid (JA). It has been reported that CI was ameliorated by JA exogenous donor methyl jasmonate (MeJA) in kinds of horticultural products, including loquat fruit, , orange fruit, pomegranate fruit, tomato fruit, ,, papaya fruit, , banana peel, kiwifruit, and peach fruit. In addition to its significant CI tolerance in diverse horticultural products, its economic and applicable characteristics make it become a promising postharvest strategy for their quality control.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl jasmonate (MeJA), the methyl ester derivative of jasmonic acid, is a signaling molecule in plant stress responses that regulates many aspects of plant development and growth including flowering, fruit ripening, and senescence (Mukkun and Singh, 2009;Rivera-Dominguez et al, 2012). MeJA is present in low concentrations in various parts of plants, including buds, shoots, leaves, flowers, fruits, and seeds, with the largest amounts present in fruits (Sayyari et al, 2011;Repčák and Suvak, 2013;Nopo-Olazabal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%